Puccini's Suor Angelica - Puccini, Giacomo; Opera Journeys Publishing (Opera Journeys libretto series, 2002)
A newly translated LIBRETTO of Puccini's SUOR ANGELICA, with many music examples.
Keywords: Puccini, Giacomo, : 1858-1924; Operas : Librettos